Carl Rogers' Humanistic Approach in Character Education in Pesantren - Wahyudi; Mahrus; Kurniyadi; Ummu Diana Munawwarah; Khoiruddin (Jurnal Pelita Raya, 2025)
This study seeks to raise collective awareness that effective character education cannot be achieved solely through verbalistic and indoctrinative instilling of values. Still, it requires emotional involvement, psychological sensitivity, and authentic relationships between educators and students as idealised by Rogers. This study uses a library research-based qualitative approach that thoroughly examines the literature related to Carl Rogers' thinking, humanistic education theory, and various academic works discussing character education in Pesantren. The results clearly state that character education in Pesantren still faces challenges in providing space for personal experiences and critical reflection among students, despite its success in building a disciplined and strong community. Carl Rogers' humanistic approach is relevant as a constructive offer because it emphasises the importance of freedom, authentic experiences, and the conscious internalisation of values. If integrated reflectively without abandoning traditional roots, it can enrich the pesantren character education model and produce a generation of santri who are obedient but also adaptive, critical, and ready to become agents of social change.